Persepsi Mahasiswa Terhadap Program Talkshow Mata Najwa Di Metro Tv(Study Deskriptif Kuantitatif Pada Mahasiswa Lpm Pabelan Ums Terhadap Mata Najwa Periode 18 November 2015 - 15 Maret 2016) - Santoso, Aris; , Budi Santoso, S.Sos, M.Si (2016)
Mata Najwa is a talk show on Metro TV program hosted Najwa Shihab aired prime time on Wednesday at 8.05 pm were the speakers news value with abundance themes. After the presidential election of 2014 this program influenced political elements. There is a change in attitude and supported programs of government policy. Therefore public perception especially students who often follow the news that happened in Indonesia, tend to have a critical perception. The purpose of this research to find out the student perceptions LPM Pabelan UMS against Mata Najwa talk show program on Metro TV the period Nov 18, 2015 - March 15, 2016. This research used a descriptive quantitative approach to collect the questionnaire as a data collection instrument. The sampling technique using total sampling technique that is the number of samples studied is the whole of the members of the population there were 30 students LPM Pabelan UMS. Data were analyzed using descriptive statistical analysis. The results of the study LPM Pabelan UMS student perception towards Mata Najwa was positive with mean 3.22. Moreover, Mata Najwa is a good talkshow program bacause not affected to critical political element before or after the presidential election of 2014. Mata Najwa upholds the roles of the media are impartial on one side, although the media owner Surya Paloh joins with Jokowi government. Keywords : Descriptive quantitative, LPM Pabelan, Mata Najwa, Perception.